Strategies to Improve the Activeness of Grade III Students in Learning Arabic Language Through the Use of Wordwall Applications: a Case Study at STAT Insanmulia - Fathin Fauziyyah; Dedih Wahyudin; Ade Arip Ardiansyah; Aditya Fitrah (UIN Sunan Gunung Djati Bandung, 2025)
The study aimed to explore the use of the Wordwall application in enhancing the engagement of third-grade students in Arabic language learning at STAT InsanMulia. The research was conducted in two cycles, with the first cycle evaluating the pre-Wordwall conditions and the second cycle after implementing Wordwall in the learning process. The qualitative research method used a case study approach. Data were collected through observations, interviews with teachers, and school documentation analysis. The results of the first cycle showed that student engagement in Arabic language learning was limited by minimal student interaction, low-quality questions, and limited innovative learning media. The second cycle revealed significant improvements in student participation, the quality of their written assignments, and deeper discussions in class. Integrating Wordwall as the main learning medium achieved a high level of satisfaction from both teachers and students, with around 95% of learning activities using Wordwall for interactive quizzes and other exercises. This study provides evidence that the use of educational technology, particularly the Wordwall application, can contribute positively to enhancing interactivity and the quality of learning in educational settings. The implications of this study emphasize the importance of developing curricula that support the use of technology in learning and the need for continuous training for teachers to optimize the potential of technology in enhancing the effectiveness of the learning process.